The Relation Between Husband Support with Exclusive Breastfeeding in Baby Age 6-12 Months in Air Dingin Health Center - Nurul Fitri; Yuniar Lestari; Lisma Evareny (Universitas Andalas, 2017)
Exclusive breastfeeding is one of ways to maintain a good growth and development for the baby. Exclusive breastfeeding in Indonesia is the right for every baby which is regulated in government regulations, but the coverage of exclusive breastfeeding is still low in some areas. The lowest exclusive breastfeeding coverage in Padang is in the working area of Air Dingin health center. The aims of this study is to determine the relationship between husbands support with exclusive breastfeeding in Air Dingin public health center.This study was a quantitative study with cross sectional design conducted at Air Dingin health centerfrom Marchto December 2017. Subject of this studywere mothers who had 6-12 month babies whichwere106 people. Data was collected by using questionnaires and guided interviews. Data analysis was performed using univariate and bivariate using chi square test with p-value ≤ 0,05.The results showed 76,4% of mothers did not provide exclusive breastfeeding for their babies and 59,4% of mothers did not get support from their husbands.Bivariate analysis showed that there was a relationship between husband support with exclusive breastfeeding with p-value=0.000.There was a relationship between husband support with providing exclusive breastfeeding for the babies. Because of the importance of husbands role, husbands must be the target for exclusive breastfeeding counseling.Therefore, husbands can also be active to find the information and participate in the success of exclusive breastfeeding for the babies.